Neuropathic Pain in Temporomandibular Joint Disorders: Case-Control Analysis by MR Imaging - Pedullà, E. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Temporomandibular joint disorders (TMJ-D) may be associated with the onset of neuropathic pain. The purpose of this study was to prospectively assess if, at the open-mouth position, the distance between the temporomandibular joint (TMJ) disk and the mandibular nerve is shorter in patients with TMJ-D and neuropathic pain vs patients with TMJ-D without neuropathic pain or in healthy people. MATERIALS AND METHODS: After ethical committee approval, we evaluated by MR imaging 16 TMJs with TMJ-D and neuropathic pain, 16 TMJs with TMJ-D without neuropathic pain, and 16 TMJs of healthy volunteers. All of the subjects were informed about the study procedure. We evaluated the distance between the TMJ disk and the mandibular nerve at the oval foramen level. Furthermore, the presence within the TMJs of internal derangement, osteoarthrosis, joint effusion, and bone marrow edema was evaluated. RESULTS: At the maximal open-mouth position, the distance between the TMJ disk and the mandibular nerve is shorter in patients with TMJ-D and neuropathic pain than in patients with TMJ-D without neuropathic pain or in healthy volunteers (P < .05). The imaging findings of TMJ internal derangement, effusion, osteoarthrosis, and bone marrow edema were present both in patients with TMJ-D without neuropathic pain and in patients with TMJ-D and neuropathic pain. CONCLUSIONS: We suggest that a closer proximity between the TMJ disk and the mandibular nerve could be one of the causes of the onset of neuropathic pain in patients with TMJ-D and neuropathic pain.